1997
DOI: 10.1128/jb.179.4.1112-1116.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and analysis of a gene cluster from Chelatobacter heintzii ATCC 29600 encoding nitrilotriacetate monooxygenase and NADH:flavin mononucleotide oxidoreductase

Abstract: Nitrilotriacetate (NTA), a synthetic chelating agent, has been used for various radionuclide processing and decontamination procedures. NTA has been codisposed with radionuclides and heavy metals to soils and subsurface sediments (4, 27, 32), where it can greatly increase the mobility of these metals in the environment by forming soluble complexes with them. Microbial degradation of NTA may ultimately aid in immobilizing these radionuclides. Several NTA-degrading bacteria have been isolated (2,7,13,18,23,42). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 44 publications
3
79
0
Order By: Relevance
“…This PAI spans a 58 kb region, and among the 44 ORFs identified it contains several virulence genes, including a complete pap gene cluster. Additionally, the authors described the R6 gene as showing a highly significant homology to a gene inside a gene cluster encoding nitrilotriacetate monooxygenase and NADH : flavin mononucleotide oxidoreductase in C. heintzii ATCC 29600 (Xu et al, 1997). By sequence alignment an ORF of 1467 bp encoding a protein of 488 aa was suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This PAI spans a 58 kb region, and among the 44 ORFs identified it contains several virulence genes, including a complete pap gene cluster. Additionally, the authors described the R6 gene as showing a highly significant homology to a gene inside a gene cluster encoding nitrilotriacetate monooxygenase and NADH : flavin mononucleotide oxidoreductase in C. heintzii ATCC 29600 (Xu et al, 1997). By sequence alignment an ORF of 1467 bp encoding a protein of 488 aa was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The R6 gene of E. coli CFT073 has recently been reported to express significant homology to a transposase gene of Chelatobacter heintzii (Xu et al, 1997). It was interesting to see whether the R6 gene fragment represented just the remnant of a transposable element or if this sequence might be involved in the regulation of Pix pilus expression.…”
Section: Nucleotide Sequence Of the Region Upstream Of Pixamentioning
confidence: 99%
“…Thermostability-Studies on the thermostability of PheA1 and PheA2 were performed by incubating the enzymes (46 M PheA1 or 48 M PheA2) in closed vials at different temperatures (50,60,70, and 85°C) in 25 mM phosphate (pH 7.0) for 2 h. At timed intervals, aliquots were withdrawn from the incubation mixtures and assayed for residual phenol hydroxylase (PheA1) and NADH:flavin reductase (PheA2) activities.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas FADH 2 most commonly serves as a redox cofactor when it is tightly bound to enzymes, free FADH 2 is used as a co-substrate for monooxygenase reactions (42)(43)(44)(45)(46), including several from E. coli strains (28,47,48). Indirect evidence has suggested that FADH 2 may also assist in the activation of ribonucleotide reductase (33).…”
Section: Nadh Is Unlikely To Be the Direct Reductant Of Free Iron-mentioning
confidence: 99%